On the best $L_1$-approximation of truncated powers by algebraic polynomials - Nitiema, P. K. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We determine the asymptotic behavior of the best $L_1$-approximations of the kernels $(x - a) + r - 1,\; 1 < r < 2,$ and the classes $W_1^r$ by algebraic polynomials.